Hydrogen and syngas production and purification technologies - Liu, Ke, 1964-; Song, Chunshan, 1961-; Subramani, Velu, 1965- (Wiley ; AIChE, 2010)
"The purpose of this multi-authored book is to provide a comprehensive source of knowledge on the recent advances in science and technology for the production and purification of hydrogen and syngas. The book comprises chapters on advances in catalysis, chemistry and process for steam reforming and catalytic partial oxidation of gaseous and liquid fuels, and gasification of solid fuels for efficient production of hydrogen and syngas and their separation and purification methods, including water - gas - shift, pressure swing adsorption, membrane separations, and desulfurization technologies"--Strana xiii
Keywords: chemická technologie; vodíkové technologie; alternativní pohonné hmoty; vodík; plynná paliva; technické plyny; zplyňování; uhlí; čištění plynů; chemical technology; hydrogen technologies; alternative propellants; hydrogen; gas propellants; technical gases; gasification; coal; gas purification; kolektivní monografie; elektronické knihy; collective monographs; electronic books